Re-framing Corporate Narratives: A Conceptual Analysis of Media Relations Strategies in Antam’s 109-Ton Gold Certification Crisis - Jestiawati; Asih Febriani; Yesi Permatasari; Pramudya Ibnu Subrata (CITACONOMIA : Economic and Business Studies, 2026)
This conceptual article examines the strategic role of media relations in navigating reputational crises triggered by digital misinformation, using the case of PT Aneka Tambang Tbk’s gold certification controversy (2024–2026). The study identifies a significant narrative distortion where administrative procedural issues were misconstrued by public perception as product integrity failures, amplified by social media algorithms. Employing a qualitative descriptive method and Situational Crisis Communication Theory (SCCT), this research analyzes how the organization transitioned from rigid legalistic rhetoric to an adaptive "Verified Authority" model. Key findings reveal that the integration of response speed, third-party validation from legal authorities, and visual education through internal digital channels was instrumental in neutralizing the "infodemic." The study highlights the strategic shift from conventional press releases to multimedia information subsidies and the importance of "searchable data" in the era of artificial intelligence. By re-framing the crisis into a momentum for public literacy, the company successfully restored institutional authority. This research contributes a new conceptual framework for state-owned enterprises to mitigate reputational risks in fragmented digital ecosystems, emphasizing that corporate sovereignty in the digital age depends on the mastery of data transparency and algorithmic management.This is an open-access article under the CC–BY-SA license.